2014
DOI: 10.3389/fmicb.2014.00287
|View full text |Cite
|
Sign up to set email alerts
|

Botulism outbreaks in natural environments – an update

Abstract: Clostridium botulinum comprises a diverse group of botulinum toxin-producing anaerobic rod-shaped spore-forming bacteria that are ubiquitously distributed in soils and aquatic sediments. Decomposition of plants, algae, and animals creates anaerobic environments that facilitate growth of C. botulinum, which may then enter into food webs leading to intoxication of animals. Via saprophytic utilization of nutrients, the bacteria rapidly sporulate, creating a reservoir of highly robust spores. In the present review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(92 citation statements)
references
References 78 publications
2
87
0
3
Order By: Relevance
“…Botulism results from exposure to a potent neurotoxin produced by the spore-forming bacterium Clostridium botulinum (22)(23)(24). There are five main kinds of botulism.…”
mentioning
confidence: 99%
“…Botulism results from exposure to a potent neurotoxin produced by the spore-forming bacterium Clostridium botulinum (22)(23)(24). There are five main kinds of botulism.…”
mentioning
confidence: 99%
“…Some BTPC toxinotypes are endemic to geographical areas or environments. Based on the literature, toxin type A is frequently isolated in North American soils west of the Mississippi River and in uncultivated soils, whereas type B prevails in soils to the east of the Mississippi, European soils and cultivated soils (Haagsma, ; Dodds, ; Espelund & Klaveness, ). Types C, D, G and C/D mosaic strains are also common in European soils, with C, D and C/D strains frequently associated with environmental botulism outbreaks.…”
Section: Pathogen Diversity and Prevalence In The Soilmentioning
confidence: 99%
“…Types C, D, G and C/D mosaic strains are also common in European soils, with C, D and C/D strains frequently associated with environmental botulism outbreaks. Type E is commonly isolated from marine environments, such as fish gut contents and coastal sediments, with research indicating this toxinotype has a higher affinity for permanently wet environments (Haagsma, ; Espelund & Klaveness, ). Lúquez et al () identified BTPC in 23.5% of 2009 Argentinean soil samples, which is high compared to the 5.7% and 16.5% prevalence found in British (Smith & Young, ) and Japanese soils (Yamakawa et al, ), respectively.…”
Section: Pathogen Diversity and Prevalence In The Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…C. perfringens has been reported in wastewater treatment systems and can be isolated from animal intestinal tracks (5, 203). C. botulinum spores are found in animal carcasses and even algal mats, where accumulation of botulinum toxin is central to human disease occurrence (204). Multiple strains of C. difficile , including those associated with disease and those less commonly found in patients, have been isolated from water and sediments.…”
Section: Transmission and Lifestyles Outside Of The Human Hostmentioning
confidence: 99%